Confirming the Clinical Safety and Feasibility of a Bundled Methodology to Improve Cardiopulmonary Resuscitation Involving a Head-Up/Torso-Up Chest Compression Technique. Issue 3 (March 2019) - Pepe, Paul E.; Scheppke, Kenneth A.; Antevy, Peter M.; Crowe, Remle P.; Millstone, Daniel; Coyle, Charles; Prusansky, Craig; Garay, Sebastian; Ellis, Richard; Fowler, Raymond L.; Moore, Johanna C.
Abstract : Objectives: Combined with devices that enhance venous return out of the brain and into the thorax, preclinical outcomes are improved significantly using a synergistic bundled approach involving mild elevation of the head and chest during cardiopulmonary resuscitation. The objective here was to confirm clinical safety/feasibility of this bundled approach including use of mechanical cardiopulmonary resuscitation provided at a head-up angle. Design: Quarterly tracking of the frequency of successful resuscitation before, during, and after the clinical introduction of a bundled head-up/torso-up cardiopulmonary resuscitation strategy. Setting: 9-1-1 response system for a culturally diverse, geographically expansive, populous jurisdiction. Patients: All 2, 322 consecutive out-of-hospital cardiac arrest cases (all presenting cardiac rhythms) were followed over 3.5 years (January 1, 2014, to June 30, 2017). Interventions: In 2014, 9-1-1 crews used LUCAS (Physio-Control Corporation, Redmond, WA) mechanical cardiopulmonary resuscitation and impedance threshold devices for out-of-hospital cardiac arrest. After April 2015, they also 1) applied oxygen but deferred positive pressure ventilation several minutes, 2) solidified a pit-crew approach for rapid LUCAS placement, and 3) subsequently placed the patient in a reverse Trendelenburg position ( 20°). Measurements and Main Results: No problems were observed with head-up/torso-up positioning ( n = 1, 489), but resuscitation rates rose significantly during the transition period (April to June 2015) with an ensuing sustained doubling of those rates over the next 2 years (mean, 34.22%; range, 29.76–39.42%; n = 1, 356 vs 17.87%; range, 14.81–20.13%, for 806 patients treated prior to the transition; p < 0.0001). Outcomes improved across all subgroups. Response intervals, clinical presentations and indications for attempting resuscitation remained unchanged. Resuscitation rates in 2015–2017 remained proportional to neurologically intact survival ( 35–40%) wherever tracked. Conclusions: The head-up/torso-up cardiopulmonary resuscitation bundle was feasible and associated with an immediate, steady rise in resuscitation rates during implementation followed by a sustained doubling of the number of out-of-hospital cardiac arrest patients being resuscitated. These findings make a compelling case that this bundled technique will improve out-of-hospital cardiac arrest outcomes significantly in other clinical evaluations.